2020
DOI: 10.1177/2331216520938929
|View full text |Cite
|
Sign up to set email alerts
|

Individual Aided Speech-Recognition Performance and Predictions of Benefit for Listeners With Impaired Hearing Employing FADE

Abstract: The benefit in speech-recognition performance due to the compensation of a hearing loss can vary between listeners, even if unaided performance and hearing thresholds are similar. To accurately predict the individual performance benefit due to a specific hearing device, a prediction model is proposed which takes into account hearing thresholds and a frequency-dependent suprathreshold component of impaired hearing. To test the model, the German matrix sentence test was performed in unaided and individually aide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 33 publications
2
20
0
Order By: Relevance
“…Although Plomp’s attenuation and distortion components are often assumed to be independent, some impairment mechanisms may, in fact, affect both speech-in-noise perception and audiometric thresholds, especially at high frequencies (Moore 2016), which is consistent with distortion type I. Schädler et al (2020) attempted to model supra-threshold auditory deficits that are independent of audibility loss. Their results suggested that reduced speech intelligibility represents an auditory perceptual deficit that may be associated with reduced tone-in-noise detection which is in agreement with the results from the current study.…”
Section: Discussionmentioning
confidence: 99%
“…Although Plomp’s attenuation and distortion components are often assumed to be independent, some impairment mechanisms may, in fact, affect both speech-in-noise perception and audiometric thresholds, especially at high frequencies (Moore 2016), which is consistent with distortion type I. Schädler et al (2020) attempted to model supra-threshold auditory deficits that are independent of audibility loss. Their results suggested that reduced speech intelligibility represents an auditory perceptual deficit that may be associated with reduced tone-in-noise detection which is in agreement with the results from the current study.…”
Section: Discussionmentioning
confidence: 99%
“…The advantage of the TEN test is that the expected masked thresholds are similar to the level of the noise (i.e., as TEN is played at 70 dB per equal rectangular bandwidth (ERB), the masked threshold is expected to be at 70 dB SPL). Although this test was originally design to detect dead cochlear regions, recent evidence suggests that tone-in-noise detection can be representative of supra-threshold deficits beyond the audiogram (Schädler et al, 2020 ).…”
Section: Extended Audiometry In Noisementioning
confidence: 99%
“…The advantage of the TEN test is that the expected masked thresholds are similar to the level of the noise (i.e., as TEN is played at 70dB per equal rectangular bandwidth (ERB), the masked threshold is expected to be at 70 dB SPL). Although this test was originally design to detect dead cochlear regions, recent evidence suggests that tone-in-noise detection can be representative of supra-threshold deficits beyond the audiogram (Schädler et al, 2020).…”
Section: Tone-in-noise Detectionmentioning
confidence: 99%